Hermes Explains : Thirty Questions about Western Esotericism - Forshaw, Peter; Hanegraaff, Wouter; Pasi, Marco (Amsterdam University Press, 2019)
Few fields of academic research are surrounded by so many misunderstandings and misconceptions as the study of Western esotericism. For twenty years now, the Centre for History of Hermetic Philosophy and Related Currents (University of Amsterdam) has been at the forefront of international scholarship in this domain. This anniversary volume seeks to make the modern study of Western esotericism known beyond specialist circles, while addressing a range of misconceptions, biases, and prejudices that still tend to surround it. Thirty major scholars in the field respond to questions about a wide range of unfamiliar ideas, traditions, practices, problems, and personalities that are central to this area of research. By challenging many taken-for-granted assumptions about religion, science, philosophy, and the arts, this volume demonstrates why the academic study of esotericism leads us to reconsider much that we thought we knew about the story of Western culture.